Eucharistic Communion and the World. - Zizioulas, John D. (Continuum International Pub. Group, 2011)
The theology of John Zizioulas presents a beautiful vision of the Church as Eucharistic communion, in which human persons both are gathered into Jesus Christ and are sent back into the world. In his previous books, Zizioulas focused on the way this communion is related to the communion of Father, Son and Holy Spirit, which calls us to understand being as communion and provides the only foundation for otherness and identity. With its sustained attention directly to the Eucharistic communion, this volume provides the context for those discussions. Zizioulas here explores the biblical dimensions.